2008
DOI: 10.1080/15367100802487499
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Stigma and Discrimination: Challenges for Social Work Practice in Psychiatric Rehabilitation and Recovery

Abstract: The recovery process and social work education share theoretical and practice roots that facilitate a goodness-of-fit between the profession and the empowerment orientation of recovery. This article examines the linkages between the recovery process and social work education, including areas where curricular renewal will assure that master's in social work (MSW) students and graduates embrace the recovery-oriented values that facilitate consumer-driven services. Curricular innovation is also proposed that addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…For example, she explains that the Code of Ethics of the National Association of Social Workers (NASW, 2000) holds among its primary values social justice and the dignity and worth of every human. Buckles et al (2008) provided an impassioned argument for including recovery ideas in MSW practice curricula, based on the recognition that recovery in mental health and social work both share an empowerment focus, and both are based on social justice (fighting stigma and discrimination).…”
Section: Conclusion and Implications For Social Work And Mental Healtmentioning
confidence: 99%
“…For example, she explains that the Code of Ethics of the National Association of Social Workers (NASW, 2000) holds among its primary values social justice and the dignity and worth of every human. Buckles et al (2008) provided an impassioned argument for including recovery ideas in MSW practice curricula, based on the recognition that recovery in mental health and social work both share an empowerment focus, and both are based on social justice (fighting stigma and discrimination).…”
Section: Conclusion and Implications For Social Work And Mental Healtmentioning
confidence: 99%
“…Recovery has been referred to as "esoteric nonsense," "hard to grasp" and "lacking an evidence base" (O'Hagan, 2004, p. 1). Providers may be continuing to support institutional practices that are inconsistent with recovery principles (Buckles et al, 2008). From a practical standpoint, some service providers are uncertain regarding what concrete changes are implied by recovery-oriented reform, if any to their day-to-day work, whereas others claim to already be implementing recovery-oriented practice (Davidson, O'Connell, Tondora, Styron, & Kangas, 2006;Dickerson, 2006).…”
Section: Challenges Of Implementing Recovery-oriented Carementioning
confidence: 99%
“…Little attention to date has been placed on providers' perspectives regarding the early stages of recovery-oriented reform and the challenges they experience in implementing recovery principles into their day-to-day practice. Such knowledge could help with the planning of education, research, and administrative practices to facilitate the transformation towards recovery-oriented care (Buckles et al, 2008). This is particularly important in countries such as Canada, where recovery is a key organizing concept for a proposed national mental health strategy (Mental Health Commission of Canada, 2009) and where organizational efforts towards implementing recovery-oriented practice are currently underway.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid stigmatization, ''label avoidance'' might become the option of choice (Buckles et al, 2008). Smith (2004) noted that ''Some disabilities can be hidden, in ways that racial identities cannot be.…”
Section: Disability Framework In the Personal Contextmentioning
confidence: 99%
“…If the person assumes the stigma is not known, the person is discreditable. Having a stigma often results in downward mobility, becomes the dominant attribute, and is internalized by the person, who prefers to be viewed as ''normal'' (Buckles et al, 2008), such that disability becomes the major aspect of the person's identity. Thompson and Ezell (2005) suggested that any term that refers to lacks in intelligence, beauty, ability, wit, and so on has negative connotations, so that although labels provide access to services and legal protection, they also identify people through a devalued characteristic, which both limits and stigmatizes.…”
Section: Disability Framework In the Personal Contextmentioning
confidence: 99%